Coastal Shipping in India Traffic Potential and Flows - Planning Commission (Planning Commission, 1981)
The report on "Coastal Shipping in India – Traffic Potential and Flows" examines the potential of coastal shipping as a cost-effective and energy-efficient alternative to rail and road transport for bulk commodities. Covering 40 coastal districts with a population of 89 million (1971), the study identifies key cargo flows including coal, salt, cement, and fertilizers. Coastal shipping demonstrates significant advantages in cost and energy efficiency, with projected traffic increasing from 8.26 million tonnes in 1981-82 to 19.85 million tonnes by 1989-90. The report highlights the importance of efficient port operations, sufficient shipping tonnage, and supportive government policies to realize the full potential of coastal shipping in India’s transport network.
Government of India Planning Commission (UNDP Transport Policy Planning Project) January, 1981
Government of India Planning Commission (UNDP Transport Policy Planning Project) January, 1981
Keywords: Coastal Shipping; India; Bulk Commodities; Traffic Potential; Ports; Coal; Cement; Fertilizers; Cost Efficiency; Energy Efficiency; Transportation Policy; Future Forecasts